Makna Visualitas Surabaya dalam Desain Jenama Cak-Cuk: Analisis Semiotik Roland Barthes - Wahyudinata, Wildan; Al Faruq, Irsyad Maulana (UI Scholars Hub, 2020)
This research aims to reveal the visual meanings behind Cak Cuk product designs. Cak Cuk is a brand of clothing and accessories from Surabaya City. Its products such as T-shirts or bags typically display various designs with Surabaya-related themes. This research used the qualitative research method by gathering and analyzing the designs displayed on various Cak Cuk products. The data, which consisted of various visual texts and verbal texts, were analyzed using concepts from Roland Barthes’ semiotic theory: denotation, connotation, and myth. The results show that both visual texts and verbal texts contained in those Cak Cuk designs represent the condition and identity of Surabaya City. These visual meanings include Surabaya’s historical association with heroism, preservation of cultural objects such as historical buildings, the tough characteristic of the Surabayans and their great sense of brotherhood, and appreciation to Surabaya’s culinary traditions.